Peranan Opinion Leader Dalam Kelompok Nelayan Pesisir - Titien Yusnita; Sarwiti S Agung; Amiruddin Saleh (Jurnal Komunikasi Pembangunan, 2016)
Fishing community is a part of Indonesian people which survives by managing fishery resources. As a society living in an offshore area, fishing community has unique social characteristics which differentiates it from land community. This study aimed to see the cause of poverty and  livelihood strategy of poor household as well as to design the community based-sustainable livelihood strategy. The literature study shows that prosperous coastal fishermen existed among poor coastal fishermen. They differed in social and economic condition. It happened because of the role of a coastal fishermen group which was capable of managing the fund got from government or another institutions. In this case the role of group leader as the opinion leader was very significant that established an effective communication.Keywords : coastal fisherman group, opinion leader